Writing on the Job : Best Practices for Communicating in the Digital Age - Coven, Martha B., 1972- (Book collections on Project MUSE., 2022)
"A practical and compact guide to writing for professionals. Writing is an essential skill in today's workplace. From messaging platforms and social media to traditional forms of communication like memos and reports, we rely on words more than ever. Given how much reading we do on mobile devices, being able to write succinctly is critical to success. Writing on the Job is an incisive guide to clear and effective writing for professionals.Martha Coven begins with the basics, explaining how to develop a professional style, get started on a piece of writing, create a first draft, and edit it into a strong final product. She then offers practical advice on more than a dozen forms of writing, from emails and slide decks to proposals and cover letters. Along the way, Coven provides a wealth of concrete examples and simple templates that make the concepts easy to understand and apply.Based on Coven's popular writing classes and workshops at Princeton University as well as her decades of experience in the public and private sectors, Writing on the Job addresses the real challenges professionals face in today's digital age, and shares essential practices that can improve the performance of any organization"--